Production of nitric oxide during graft rejection is regulated by the Th1/Th2 balance, the arginase activity, and L-arginine metabolism - Holán, Vladimír; Pindjáková, Jana; Krulová, Magdaléna; Neuwirth, Ales; Fric, Jan; Zajícová, Alena (Transplantation, 2006)
BACKGROUND: Production of nitric oxide (NO) by graft infiltrating macrophages has been proposed as an important effector mechanism of allograft rejection. Although high levels of NO are generated during allograft rejection, undetectable or only limited amounts of NO were found in rejected skin xenografts. METHODS: BALB/c mice were grafted with skin transplants from syngeneic, allogeneic or xenogeneic (rat) donors. The production of NO, cytokines and arginase in the grafts was determined by spectrophotometry, enzyme-linked immunosorbent assay, or polymerase chain reaction. Effects of depletion of CD4+ cells, neutralization of interleukin (IL)-4 or application of arginase inhibitors N(omega)-hydroxy-L-arginine (L-NOHA) and L-valine on production of NO in rejected xenografts were evaluated. RESULTS: Rejection of rat skin xenografts, on the contrary to rejection of allografts, was associated with a local high production of Th2 cytokines IL-4 and IL-10, overexpression of arginase genes, strongly enhanced arginase activity and attenuated NO generation in the graft. The supernatants obtained after cultivation of skin xenograft (but not allograft or syngeneic graft) explants contained a high arginase activity and strongly suppressed NO production by activated macrophages. This suppression was completely inhibited by L-NOHA or was overcome by an excess of exogenous L-arginine, a substrate for NO synthesis. Cocultivation of xenograft explants that did not produce NO with arginase inhibitors L-NOHA or L-valine restored NO generation in the graft. CONCLUSION: The results suggest that upregulation of arginase activity by Th2 cytokines during xenograft rejection limits the bioavailability of L-arginine for the inducible NO synthase and thus attenuates generation of NO by the graft-infiltrating macrophages.
Keywords: Nitric Oxide; Skin Transplantation; Transplantation, Heterologous; Male; Th1 buňky; Transplantation, Homologous; interleukin-10; Gene Expression Regulation, Enzymologic; Arginase; oxid dusnatý; mužské pohlaví; kůže; Arginine; Graft Rejection; Interleukin-10; techniky tkáňových kultur; Th1 Cells; interleukin-4; Interleukin-4; krysa rodu Rattus; homologní transplantace; Animals; ženské pohlaví; Skin; regulace genové exprese enzymů; zvířata; Th2 Cells; makrofágy; Rats; rejekce štěpu; myši; arginin; Th2 buňky; arginasa; Mice; transplantace kůže; Female; Macrophages; Tissue Culture Techniques; transplantace heterologní